Nicolau syndrome of the scalp in a 5-month-old little girl. - Krishnegowda, R.; Deshmukh, N. (European Journal of Pediatric Dermatology, 2023)
Nicolau syndrome, also known as embolia cutis medicamentosa, is an iatrogenic condition characterized by intense vasospasm, thrombus formation, or compression of the skin vasculature leading to necrosis and ulceration. We describe a case of Nicolau syndrome in an uncommon site – scalp – after phlebotomy in a 5-month-old little girl with consequent necrosis and secondary ulceration. This syndrome should be kept in mind when performing routine invasive procedures such as intramuscular injection, intravenous access, etc.